KPJ Johor Specialist Hospital / Zulaikha Zainal - Zainal, Zulaikha (Faculty of Business and Management, 2023)
This report is about SWOT Analysis for the company that I been intern for 6 months. Firstly, I managed to get the department that aligned with the major that I studied which is Business Administrator (Human Resource). I internship at KPJ Johor Specialist Hospital which is a private hospital. Through this 6 month I need to analysis their strength, weakness, opportunity and threats for the company. As through that, I can get to know more on how to make SWOT analysis and at the same time get to know more how the company work especially the environment. For this report I gathered all the information from the internet and get the data from my HR manager in order to complete and have the evidence for my point. In this report it has company profile where it is a background of the company then continue with organizational culture where it has the organizational chart of the company then details about the services of the company then continue with the SWOT analysis and recommendation for each SWOT and conclusion.